ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA - Maria D. Don Rena; Farida Daniel; Prida N. L. Taneo (IKIP Siliwangi, 2020)
The purpose of this study was to determine the ability of students' mathematical connection in solving story problems. The research method used is descriptive qualitative. The study was conducted in junior high school Christian Soe 1with the source of the data was a student of class VII B as many people as 27 people. Data collection techniques using observation, mathematics connection ability test and interviews. The research instrument was observation sheets, mathematical connection ability questions and interviews. The research instruments were observation sheets, mathematical connection ability questions, and interview guidelines. Data analysis techniques include Miles and Huberman models with data validity testing using the technique triangulation model. The results of the analysis show that students' high mathematical connection ability of students in solving story problems is high for indicators looking for the relationships of various representations of concepts and procedures, understanding relationships between mathematical topics, understanding the equivalent percentage of a concept and looking for relationships of one procedure with other procedures in equivalent representation while low for indicators of applying mathematics in other fields of study or in everyday life as well as in applying relationships between mathematical topics with topics outside mathematics.